Resveratrol attenuates the Na(+)-dependent intracellular Ca(2+) overload by inhibiting H(2)O(2)-induced increase in late sodium current in ventricular myocytes. - Chunping Qian; Jihua Ma; Peihua Zhang; Antao Luo; Chao Wang; Zhiqiang Ren; Linghao Kong; Shuo Zhang; Xiaojing Wang; Ying Wu (PLoS ONE, 2012)
BACKGROUND/AIMS: Resveratrol has been demonstrated to be protective in the cardiovascular system. The aim of this study was to assess the effects of resveratrol on hydrogen peroxide (H(2)O(2))-induced increase in late sodium current (I(Na.L)) which augmented the reverse Na(+)-Ca(2+) exchanger current (I(NCX)), and the diastolic intracellular Ca(2+) concentration in ventricular myocytes. METHODS: I(Na.L), I(NCX,) L-type Ca(2+) current (I(Ca.L)) and intracellular Ca(2+) properties were determined using whole-cell patch-clamp techniques and dual-excitation fluorescence photomultiplier system (IonOptix), respectively, in rabbit ventricular myocytes. RESULTS: Resveratrol (10, 20, 40 and 80 µM) decreased I(Na.L) in myocytes both in the absence and presence of H(2)O(2) (300 µM) in a concentration dependent manner. Ranolazine (3-9 µM) and tetrodotoxin (TTX, 4 µM), I(Na.L) inhibitors, decreased I(Na.L) in cardiomyocytes in the presence of 300 µM H(2)O(2). H(2)O(2) (300 µM) increased the reverse I(NCX) and this increase was significantly attenuated by either 20 µM resveratrol or 4 µM ranolazine or 4 µM TTX. In addition, 10 µM resveratrol and 2 µM TTX significantly depressed the increase by 150 µM H(2)O(2) of the diastolic intracellular Ca(2+) fura-2 fluorescence intensity (FFI), fura-fluorescence intensity change (△FFI), maximal velocity of intracellular Ca(2+) transient rise and decay. As expected, 2 µM TTX had no effect on I(Ca.L). CONCLUSION: Resveratrol protects the cardiomyocytes by inhibiting the H(2)O(2)-induced augmentation of I(Na.L.)and may contribute to the reduction of ischemia-induced lethal arrhythmias.